1994
DOI: 10.1111/j.1365-2249.1994.tb06102.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry CD4+/CD8+ ratio of liver-derived lymphocytes correlates with viral replication in chronic hepatitis B

Abstract: SUMMARY T lymphocytes have been assumed to play an essential role in tissue injury in patients with chronic hepatitis B. As hepatitis B virus (HBV) is considered as a major factor controlling liver inflammation, we assessed whether a particular T lymphocyte subset could be preferentially detected in the liver in accordance with viral replication. Liver‐derived lymphocytes and peripheral blood lymphocytes were analysed by flow cytometry in 21 patients with histologically confirmed chronic hepatitis B without ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…There was no correlation between the CD4'/CD8^ ratio of liver-derived lymphocytes and the CD4*/CD8+ ratio of peripheral blood lymphocytes. This supports our previous results [27], thereby indicating that lymphocytes we collected from the liver do not reflect blood contamination and assuming Ihat the peripheral blood T cell population may not be represertativc of events occurring in liver tissue.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There was no correlation between the CD4'/CD8^ ratio of liver-derived lymphocytes and the CD4*/CD8+ ratio of peripheral blood lymphocytes. This supports our previous results [27], thereby indicating that lymphocytes we collected from the liver do not reflect blood contamination and assuming Ihat the peripheral blood T cell population may not be represertativc of events occurring in liver tissue.…”
Section: Discussionsupporting
confidence: 89%
“…It has been suggested that T lymphocytes mediate liver cell necrosis [40]. Recently, we have shown that CD4 V<-'D8' ratio of liver-derived lymphocytes but not the percentage of 7/5 TCR T cells or that of CD2^CD57+ correlates with HBV replication in patients with chronic hepatitis B [27]. Therefore, it is tempting to suggest that, in comparison with chronic hepatitis B, liver cell lesions in HCV-infected patients are related to immune-mediated mechanisms.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Boni et al [32][33][34][35] reported that antiviral treatment can overcome CD8 + T cell hypo-responsiveness in subjects with chronic HBV infection, suggesting that the T cells are present, but suppressed. It was reported by Pham et al [36] in 21 CHB patients that the ratio of CD4 + / CD8 + liver-derived lymphocytes, and not of peripheral blood lymphocytes appeared to be related to the level of HBV replication, and it revealed a positive correlation with viral load. The evidence that efficient antiviral T cell response can be restored by mono-antiviral treatment in CHB patients concurrently with reduction of viremia, indicates the importance of viral load in the pathogenesis of T cell hypo-responsiveness in these patients.…”
Section: Discussionmentioning
confidence: 84%
“…Boni et al [38,39] have reported antiviral treatment can overcome CD8 + T-cell hyporesponsiveness in subjects with CHB, which suggests the T cells are present but suppressed. It has been reported by Pham et al [40] in 21 CHB patients that the ratio of CD4 + /CD8 + liver-derived lymphocytes, but not of peripheral blood lymphocytes, appears to be related to the level of HBV replication, which reveals a positive correlation with viral load. The evidence that an efficient antiviral T-cell response can be restored by antiviral monotherapy in CHB, concurrently with reduction of viremia, indicates the importance of viral load in the pathogenesis of T-cell hyporesponsiveness.…”
Section: Figurementioning
confidence: 81%